PENANAMAN NILAI CINTA TANAH AIR TERHADAP PENYANDANG TUNAGRAHITA - Huda, Fatakhul; Faizah, Siti Khusnul; Supriyanti, Iin (Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ngabar Ponorogo, Indonesia, 2017)
This study aims to determine: (1) to cultivate the value of love of the homeland (keeping the personal hygiene and environment) against people with mentally disabled in the Village Karangpatihan, Balong district, Ponorogo regency (2) the response of people with disabilities in applying homeland love by maintaining personal hygiene and environment in Karangpatihan Village, Balong Sub-district, Ponorogo Regency (3) the inhibiting and supporting factors in applying the value of love of the homeland (maintaining personal hygiene and environment) to people with mentally disabled in Karangpatihan Balong Ponorogo. The research method used is qualitative research by using case study approach. The research was conducted in Karangpatihan Balong Ponorogo. While the data sources in this study are: Mr. Village head Karangpatihan Balong Ponorogo and his staff, close family with people with mentally disabled in the village Karangpatihan Balong Ponorogo and people with mentally disabled in the village Karangpatihan Balong Ponorogo. The data were collected using observation, interview, and documentation. Observations are used to (a) Observe the environmental conditions of the mentally disabled village. (b) Observe the facilities available to support the activities of persons with disabilities in making batik cloth and mat. (c) Observing the daily activities of mentally disabled, especially the care of people with disabilities in maintaining cleanliness of the environment and personal hygiene. (d) Observing the results of community empowerment for people with mental health. (e) Ensure the existence of schools for children with disabilities. The results of the research are: the Karangpatihan Village is very concerned about its citizens, especially residents who bear mentally disabled. Because implanting the value of nationalism is very important for the survival of citizens. Proven with them can come on time, they memorized the schedule gathered at home hope. In addition, the way they dress also shows high enthusiasm, this is evidenced by clean clothes and clean body. One of the supporting factors is the counseling done by the village apparatus and cooperation with the Community Health Centers or other parties who voluntarily assist the people with the mentally disabled, while the inhibiting factor is the emotional condition of persons with unstable mentally disabled, the economic condition of persons with the mentally disabled who are classified as middle to down, and a mentally disabled house that is a distance away from the house of hope.